(untitled) (قضايا سياسية, 2022)
The world lives since 1980s of the past century, the technological revolution in the media, information and communication, and the most important of its results is the widely spread of the Internet. where the "cyber space " which includes data, information and networks, transferred to a environment of global interactions. The methods and tools of terrorism change over time, as they do not remain in the same format. As a result of developments in technology in the area of information and communication; emerged as " cyber space terrorism " as a challenge and a new global crisis. the Internet became a new environment of" cyber-attacks" which is targeted to destroy or disable websites to intimidate governments or peoples for political, religious, ideological or social reasons. As well as it's the exploitation by the terrorist groups, to serve their purpose different. the international attention to combating the "cyber terrorism" increased through the adoption of policies, laws and procedures at the national level and at international level of cooperation as a result of the risks of "cyber-attacks" and its great threat.